Forwarding of Messages Via WhatsApp: The Mediating Role of Emotional Evocativeness - Bakare, A.S.; Owusu, A.; Abdurrahaman, D.T. (Howard Journal of Communications, 2021)
WhatsApp facilitates easy communication as users can send messages. images, videos, and group conversations instantly. Forwarding the messages received is one of the desires of WhatsApp users. Hence, it is imperative to understand the key determinants of this phenomenon. This study examine the level of influences of entertainment, purposive value, social identity, and emotional evocativeness on the decision to forward received messages via WhatsApp. Using a random sampling method, primary data was obtained from 342 respondents from a Private University in Cyberjaya, Malaysia. The data was analyzed through Partial Least Square Structural Equation Modeling (PLS-SEM) using SmartPls. Findings show that infotainment does not affect the decision to forward WhatsApp messages; however, purposive value, social identity and emotional evocativeness have significant effects. Similarly, while emotional evocativeness mediates between purposeful value, social identity, and the decision to forward WhatsApp messages, it does not mediate between infotainment and the decision to forward WhatsApp messages. These findings will help users understand the key elements that should be implemented to achieve virality for WhatsApp messages and other social media. Limitations, future study opportunities and practical and theoretical implications also discussed
Research Article
Keywords: infotainment; purposive value; WhatsApp message